PENGEMBANGAN MODUL MIKRO KONSELING SPIRITUAL COGNITIVE FAITH THERAPY (SCFT) UNTUK MENGATASI STRES AKADEMIK PADA MAHASISWA - Yuwono, Sudharno Dwi; Agustini, Ninik Elsa; Diyanto, Febri Al; Darma, D (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
In the laboratory practicum phase, supporting learning tools such as practicum modules are required. The module is designed to provide step-by-step guidance in understanding the basic concepts of counseling, applying relevant techniques, and evaluating the practiced sessions. This module is expected to have an impact on the implementation of measurable practicum activities. Therefore, this micro-counseling module was developed to be specific. The approach chosen is the result of integration between the rational emotive behavioral therapy approach and the Islamic counseling approach which is packaged with the term spiritual cognitive faith therapy (SCFT) and focuses on the problem of academic stres. This type of research is a development research that aims to produce products in the form of modules. Module development uses the 4D model, namely define, design, develop, and disseminate.  The developed product is included in the very feasible category, with an ideal level of 93% from the material aspect and 100% from the media aspect. However, the developed product is still at the hypothetical stage, so further effectiveness testing is needed to ensure its usefulness by the development objectives.